자기보존과 자살금지: 홉스, 스피노자, 칸트를 중심으로 - 이유택; Lee Yu-taek (칸트연구, 2025)
자살금지의 합리적 근거는 존재하는가? 본고는 이 물음에 대한 대답을 ‘자기보존’을 철학적 사유의 근간으로 삼았던 세 명의 철학자, 즉 홉스와 스피노자, 그리고 칸트에게서 찾는다. 홉스에게 자기보존은 선이고, 죽음은 악이다. 인간이 죽음을 회피하고, 자기보존을 지향하는 것은 너무나 당연한 것이다. 자기보존의 욕망에는 필연적으로 이성의 자살금지 명령이 포함되어 있다. 그러나 홉스가 말하는 이성의 자살금지 명령은 예외를 허용한다. 죽음이 악이 아니라, 오히려 선인 경우도 존재하기 때문이다. 스피노자에게 이성의 자기보존 명령은 자명한 사실이다. 이성의 본질이 자기보존인 한, 합리적 자살의 가능성은 원천적으로 차단된다. 스피노자의 관점에서 볼 때 자살은 자기보존의 이성 명령을 위반하는 ‘반이성적’ 행위이다. 이러한 주장의 정당성을 스피노자는 두 개의 명제, 즉 “사물은 외부의 원인에 의하지 않고서는 파괴될 수 없다.”와 “각각의 사물은 자신 안에 존재하는 한에서 자신의 존재 안에 남아 있으려고 한다.”는 명제로부터 연역적으로 도출하고 있다. 칸트에게 자기보존은 인간의 도덕적 의무이다. 자살은 이러한 도덕적 의무를 위반하는 행위이며, 목적 달성을 위해 자기를 수단화하는 ‘자기살해’ 행위이다. 그러므로 자살은 금지되어 마땅한 ‘반인륜적’ 행위이다. 어떤 인간도 인륜성을 파괴할 권리를 가지고 있지 않다. 칸트에게 인륜성은 ‘목적 그 자체’를 뜻하며, 모든 인간은 이러한 인륜성을 보존해야 할 보편적 책임을 가지고 있다. Is there a rationale for “prohibition of suicide”? This study attempts to answer this question by examining three philosophers who made “self-preservation” the fundament of their philosophical thinking: Hobbes, Spinoza, and Kant. For Hobbes, self-preservation is good and death is evil. It is natural that people avoid death and pursue self-preservation. The desire for self-preservation necessarily includes the rational prohibition of suicide. However, Hobbes’ rational prohibition of suicide allows for exceptions, and there are cases in which death is not evil, but good. For Spinoza, the imperative of self-preservation of reason is self-evident. As long as the essence of reason is self-preservation, the possibility of rational suicide is fundamentally blocked. From Spinoza’s perspective, suicide is an “irrational” act that violates the rational imperative of self-preservation. Spinoza deduces the validity of this claim from two statements: “Things can only be destroyed by external causes” and “Everything, insofar as it exists in itself, seeks to remain in its own being.” For Kant, self-preservation is a moral duty of human beings. Suicide - an act of “self-murder” that uses oneself as a means to achieve a goal - violates this moral duty. Therefore, suicide is an “inhumane” act that should be prohibited. No human being has the right to destroy humanity. For Kant, humanity is an “end in itself,” and all human beings share the universal responsibility for its preservation.